Economic analysis of forced tomato production with regard to the intensity of production - Dorogi, D. A.; Apáti, F. (International Journal of Horticultural Science, 2019)
We assessed the cost/income conditions of forced tomato production and return conditions of the growing technologies by investment-profitability analysis. Horticultural sectors generate significant added value and employ a large number of workers per unit area; however, these sectors cover only 4% of agricultural areas. Regarding the use of capital and labour, forced vegetables are the most intensive horticultures with several development potential and reserves to gain better quality and a more efficient farming. One of the most prominent forced cultures is table tomato produced under different types of forcing equipment in Hungary: traditional, low-height plastic tunnel; large-atmospheric, block-based plastic tunnels and various greenhouses. The prime goal of my thesis is to specify the economic efficiency of each type and to choose the most efficient one by the complex economic assessment of plastic tunnels, block-based plastic tunnels and greenhouses with the most advanced technologies. Results of the economic analysis suggest that the most efficient production method is the modern, Dutch greenhouse technology; however, this statement is not backed by every indicator: each type has its own advantages and disadvantages. Regarding the future, the installation of such types or even (in the technical sense) more modern growing technology may be considered as a prospect for capital intensive and larger businesses.